Analiza razvoja govornih spretnosti in pri tem pojavljajočih se oblikoslovno-skladenjskih nepravilnosti pri mlajših in starejših začetnikih učenja nemškega jezika - Brumen, Mihaela (Jezik in slovstvo, 2002)
Mental operations underlying the acquisition of the first and all the subsequent languages are similar. On the other hand, ways of getting familiar with individual languages and their specific properties, emotional responses and personal experiences in the process vary. The paper outlines the development of language skills and of morphological and syntactic errors in younger (ages 9-11 years) and older (ages 11-13 years) beginner learnes of German in two Slovene primary schools. Language competence of pupils in the two experimental groups (early beginners vs. older beginners) is compared
Keywords: German; nemščina; učenje jezika; tuji jeziki; jezikovne napake; začetni pouk